Investigation of Intelligent Vehicle Path Tracking Based on Longitudinal and Lateral Coordinated Control - Zeyu Sun; Ruochen Wang; Qing Ye; Zhendong Wei; Bingqing Yan (IEEE Access, 2020)
In this paper, a new longitudinal and lateral coordinated control algorithm for the intelligent vehicle (IV) is proposed for the problem of unbalance of tracking accuracy and vehicle stability during path tracking process. This work proposes a novel algorithm that adopts hierarchical control architecture and local linearization of the nonlinear path tracking model, establishes the objective function by tracking performance and driving performance in the tracking process, and designs the upper optimal controller. Following the theory of fuzzy proportional-derivative control method, a low-speed tracking controller is designed to track the desired speed. Simulations and the hardware-in-the-loop test are utilized to verify the effectiveness of the designed path tracking control algorithm. Results show that, unlike the traditional fixed-speed tracking control method, the proposed vertical and horizontal coordinated control algorithm can guarantee the vehicle's tracking performance at different speeds and improve its form stability. The improved effect is evident even at high speed.